1997
DOI: 10.1016/s0954-6111(97)90045-7
|View full text |Cite
|
Sign up to set email alerts
|

Elevated serum angiotensin converting enzyme levels in metastatic ovarian dysgerminoma

Abstract: A case of a 32-year-old XY genotype female is described, presenting with mediastinal and abdominal lymphadenopathy and associated with an elevated serum angiotensin I converting enzyme (SACE) level. Lymph node histology showed a malignant dysgerminoma of ovarian origin. Combined chemotherapy led to a radiological regression of the lymphadenopathy and coincided with a decrease in SACE concentration. The authors suggest that SACE may be a marker for disseminated germinoma tumours and may be useful for monitoring… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

1998
1998
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 5 publications
0
5
0
1
Order By: Relevance
“…In this study by Erman et al [18], it was speculated that the cause of the increased ovarian ACE activity was not clear, but may be related to the aging process. Cotter et al [19] reported a patient with elevated serum ACE levels in metastatic ovarian carcinoma and suggested that serum ACE may be a marker for disseminated germinoma tumors and may be useful for monitoring treatment. In conjunction with this suggestion, we think that based on our results ACE might be a useful marker also in epithelial OC patients.…”
Section: Discussionmentioning
confidence: 99%
“…In this study by Erman et al [18], it was speculated that the cause of the increased ovarian ACE activity was not clear, but may be related to the aging process. Cotter et al [19] reported a patient with elevated serum ACE levels in metastatic ovarian carcinoma and suggested that serum ACE may be a marker for disseminated germinoma tumors and may be useful for monitoring treatment. In conjunction with this suggestion, we think that based on our results ACE might be a useful marker also in epithelial OC patients.…”
Section: Discussionmentioning
confidence: 99%
“…As for epithelial OC patients, serum ACE levels do not vary according to patient stage and pathological subtype. This situation suggests that serum angiotensin I converting enzyme may be a marker of disseminated germinoma (85).…”
Section: Ovarian Cancermentioning
confidence: 97%
“…No differences were observed between the stage of the tumor (FIGO I–II vs. FIGO III–IV) as well as between serous and non-serous OC patients [ 94 ]. Cotter et al [ 95 ] suggested on the basis of case report patients with metastatic ovarian carcinoma that serum ACE1 level may be a marker for ovarian germ cell tumors (dysgerminoma) and may be useful for monitoring treatment [ 95 ]. On the other hand, Correa-Noronha et al [ 96 ] did not observe an association between the insertion/deletion (I/D) polymorphism in the angiotensin-converting enzyme (ACE) gene and epithelial OC [ 96 ].…”
Section: Ovarian Diseases Related To the Ace2/ang-(1-7)/mas1 Axismentioning
confidence: 99%